Periphytic Biofilm Formation on Natural and Artificial Substrates: Comparison of Microbial Compositions, Interactions, and Functions - Miao, Lingzhan; Wang, Chengqian; Adyel, Tanveer M.; Zhao, Jiaqi; Yan, Ning; Wu, Jun; Hou, Jun (Frontiers in Microbiology, 2021)
Periphytic biofilms have been widely used in wastewater purification and water ecological restoration, and artificial substrates have been progressively used for periphyton immobilisation to substitute natural substrates. However, there is insufficient knowledge regarding the interaction network structure and microbial functions in biofilm communities on artificial substrates, which are essential attribute affecting their applications in biofilm immobilisation. This study compared the community structure, co-occurrence network and metabolic functions of bacterial and microeukaryotic periphytic biofilms during a 35-day indoor cultivation on artificial substrates, such as artificial carbon fibre (ACF) and polyvinyl chloride (PVC), and natural substrates, such as pebble and wood. Results demonstrated that different types of artificial substrates could affect the community composition and functional diversity of bacterial and microeukaryotic biofilms. The bacterial and microeukaryotic community on ACF and PVC showed significantly higher Simpson index compared to those on wood. Bacterial networks on artificial substrates were more complex than those on natural substrates, while the keystone species on natural substrates were more abundant, indicating that the bacterial communities on artificial substrates had stronger stability and resistance to external interference. Furthermore, the functional metabolic profiles predicted showed the abilities of bacterial communities to metabolise nitrogen and carbon sources colonised on artificial substrates were stronger than those on natural substrates. These findings demonstrated that artificial substrates could be special niches for microbial colonisation, possibly altering microbial compositions, interactions and functions. Therefore, this study provides a powerful theoretical basis for choosing suitable artificial substrates for microbial aggregation and immobilisation technology.